MENERAPKAN BUDAYA LITERASI GURU SEKOLAH DALAM UPAYA MENINGKATKAN PENDIDIKAN DI ERA INDUSTRI 4.0 - Meliantina Meliantina (Muróbbî: Jurnal Ilmu Pendidikan, 2019)
Abstract: In the industrial era 4.0, especially in the world of education, the teacher is an educator who is obliged to educate his students in learning skills, by: First, Educational competence, educational competence or internet-based learning of things as basic skills. Second, Competence for technological commercialization, has the competence to bring students to have an entrepreneurship attitude based on technology and students' work of innovation. Third, Competence in globalization, a world without insulation, does not stutter about various cultures, hybrid competence and problem solving competence. Fourth, Competence infuture strategies, the world is easy to change and runs fast, so it has the competence to predict exactly what will happen in the future and the strategy. Fifth, Competence counselor, considering that in the future the child's problem is not the difficulty in understanding teaching material, but more related to psychological problems, stress due to the increasingly complex and severe state of pressure, it takes a teacher who is able to act as a counselor / psychologist. Why do you say the teacher because some people assume all fields of teachers must be mastered even though sometimes we cannot lie to ourselves, if we must master all fields we might not be able to, but there is no harm if these shortcomings must be covered by lifelong learning.